Potential of endophytic bacteria from rice root as potassium solvent - WARZATULLISNA WARZATULLISNA; LENNI FITRI; YULIA SARI ISMAIL (Society for Indonesian Biodiversity, 2019)
Abstract. Warzatullisna, Fitri L, Ismail YS. 2019. Potential of endophytic bacteria from rice root as potassium solvent. Biodiversitas 20: 1303-1308. Endophytic bacteria live in plant tissues and known to have many benefits for plant growth. One function of endophytic bacteria are known to be able to dissolve potassium. Potassium is one of the macronutrients that plays an important role in plant growth and development. This study aims to obtain endophytic bacterial isolates from the roots of rice plants (Oryza sativa L.) which have potential as potassium solvents, identify the endophytic bacteria in morphologically and physiologically, and analysis of the selected isolate 16S rRNA genes. Selected endophytic bacterial isolates from the test of dissolving potassium on medium Alexandrov, measured clear zone using calipers and continued with biochemical tests using KIT DL-96E also identified based on 16S rRNA gene and compared for their close relationship with reference strains available in the Bank Genes. Based on the isolation results, 7 isolates from the roots of rice were obtained. Six isolates of endophytic bacteria were able to dissolve potassium. EPK3 isolates were the isolates that are capable of dissolving the highest potassium in Alexandrov media with a 17.9 mm potassium dissolution index. EPK3 isolates also produce inhibit the growth of Xanthomonas oryzae with a 1.2 mm inhibition zone. Physiological identification showed that EPK3 isolates were Enterobacter cloaceae bacteria with 93.79% of similarity. Based on the 16SrRNA gene showed that EPK3 isolates were closely related to E. cloaceae strain SBP-8 with similarity rate is 99%.